Evaluasi Penetapan Dan Penagihan Pajak Bumi Dan Bangunan Kabupaten Kepulauan Talaud - Jefandri Lulage; Harijanto Sabijono; Steven J. Tangkuman (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
The porpose of this study was to evaluate the determination and collection of land and building taxes in the Talaud Island Regency. This research belongs to the type of analytical descriptive research or explanatory research which is realized by describing the reality or condition of an object in the form of a sentence description based on information from parties directly related to this research. The result of the study indicate that the determination of the value of land and building taxes in the Talaud Island Regency has been carried out in accordance with the Regent’s Regulation no. 25 of 2013 concerning Procedures of collecting Article 10 land and building taxes, which are stipulated in accordance with Law 28 of 2009 concerning Regional Taxes and Regional Levis Article 79. In carrying out the collection of land and building taxes, the Talaud Island Regency Regional Tax and Levy Management Agency as PBB manager has collected land and building tax (PBB) in accordance with the provinsions of the legislation, namely the regulation of the Regent of the Talaud Island Regency Number 25 of 2013 concerning Procedures for Collection of Land and Building Taxes Article 20 and PP Number 55 of 2016 concerning General Provisions and Procedures for collecting Regional Taxes Article 19.